Investigation on Stator Winding Inter-turns Short Circuit Fault Diagnosis - ZHAO Hong-sen; GE Bao-jun; TAO Da-jun; YANG Kun; XING Guang (Journal of Harbin University of Science and Technology)
On the basis of negative sequence current generation mechanism analysis of synchronous generator stator winding inter-turns short circuit，the method of detecting and diagnosing synchronous generator stator winding inter-turns short circuit is proposed，which uses the negative sequence current as fault signature. A field-circuit coupled mathematical model of synchronous generator is built，based on the field-circuit coupled principle. Firstly， stator winding inter-turns short circuit happened in synchronous generator with half load is simulated. And then three-phase current phase difference，amplitude and negative sequence current component before and after fault is calculated according to the model. The accuracy of model and rationality of theoretical analysis is demonstrated by the use of experimental data coming from 24 kW synchronous. Meanwhile，the short circuit fault with the same branch and different branch impact on the negative sequence current is also simulated and analyzed. The results have some significance for synchronous generator stator winding inter-turns circuit fault monitoring and diagnosis.